The effects of neglecting the study of soil sounding on foundations - Souza, Lyvia Monteiro Advincula de; Carvalho, Beatriz Melo; Oliveira, Cláudio Bonfante de (Seven Editora, 2023)
Soil sounding aims to bring essential information so that the structural calculator can design a structure that effectively meets the needs of each type of construction. However, in numerous situations (especially in small constructions) this information is neglected since the owner usually reports that it is something impractical. Among this information obtained, is the designation of the type of soil, the level of the water table, the layers of the soil, and their respective resistances. Obtaining this information, it is possible to define the type of foundation most compatible with the construction in question, as this is one of the crucial parts of construction since it is where all the loads of the building are supported, therefore it plays a considerable role in the staticity of the building. There are constant problems in the foundation because this previous study of the soil has not been carried out. As a result, professionals rely on the study of soil sounding, a method of geotechnical investigation that helps in the identification of soil layers. This work aims to show the effects of negligence in the study of soil sounding in foundations. DOI:https://doi.org/ 10.56238/devopinterscie-152